Effects of temperature, salinity and dissolved oxygen on excystment of podocysts in the edible jellyfish Rhopilema esculentum Kishinouye, 1891 - Fu, Zhide; Xing, Yixuan; Gu, Zhifeng; Liu, Chunsheng; Chen, Siqing (Indian Journal of Fisheries, 2019)
The scyphozoan jellyfish Rhopilema esculentum Kishinouye, 1891 is a species occurring in the traditional fishery in China. However, the yield of this species in fishery has rapidly declined since 1980s. The podocyst is an important phase during asexual reproduction in Scyphozoa and is considered to be potentially important to the population dynamics of jellyfish. In this study, we investigated the microstructure and effects of environmental factors on the excystment of podocysts. Podocysts of greater than 8 months of age exhibited no morphological differences compared to newly formed podocysts. Following excystment, a smooth-edged hole, probably created by enzymatic digestion was observed. Excystment sharply increased when the water temperature was higher than 18°C, suggesting that temperature ranging from approximately 13-18°C triggers the excystment of podocysts in R. esculentum. Stepwise temperature variation suggested that cooling was much more effective than warming in the induction of R. esculentum podocysts to excyst. The optimal salinity and dissolved oxygen (DO) conditions for excystment were observed to be 20‰ and 6 mg O2 l-1 respectively. Furthermore, excystment was suppressed by both stepwise increase and decrease in salinity or DO. Though R. esculentum podocysts could survive extreme environmental conditions such as hypoxia and low salinity, excystment rates were markedly reduced compared to those of other bloom jellyfish species when the DO and salinity levels were returned to normal.